Guidelines prescribed by general practitioners to patients with acute low back pain regarding ‘return to work’ - Petronella A. Hough; Francois C. Van Rooyen; Elizna Bredenkamp; Kira Brough; Mariska Ferreira; Helene Myburgh; Chantel Snyman; Celia van Niekerk (South African Family Practice)
Background: The traditional treatment protocol for acute low back pain (ALBP) primarily used by healthcare professionals has in the past decade been strict bed rest, corsets, traction and ‘back schools’. However, current research has led to dramatic changes in the traditional treatment protocol. The literature suggests that the protocol should be replaced by parsimonious imaging, early return to normal activities and greater emphasis on exercise to prevent recurrences of ALBP and to treat chronic pain. The aim of this study was to investigate the guidelines prescribed by general practitioners (GPs) to patients with acute low back pain (ALBP) regarding ‘return to work’.